Rabbit polymorphonuclear leukocytes do not secrete endogenous pyrogens or interleukin 1 when stimulated by endotoxin, polyinosine:polycytosine, or muramyl dipeptide. - Windle, B E (1983)
Rabbit polymorphonuclear leukocytes were purified from rabbit blood by centrifugation on colloidal silica gradients followed by sedimentation in 4% Ficoll. The purified neutrophils had normal random motility, responded to chemotactic stimuli, phagocytosed zymosan particles, made superoxide, and phagocytosed and killed bacteria. However, they did not secret endogenous pyrogens either spontaneously or in response to stimulation with endotoxin, polyinosine:polycytosine, or muramyl dipeptide. Macrophages isolated on the same gradients secreted some pyrogen spontaneously and secreted considerably more in response to the same three stimuli. This evidence reinforces the idea that macrophages are the only source of endogenous pyrogens, and that pyrogens secreted by cell populations that are rich in neutrophils are to be attributed to the monocytes or macrophages that the cell populations contain.